ANALISIS PENGARUH NIM, BOPO, LDR DAN NPL TERHADAP PROFITABILITAS PADA BANK PEMERINTAH DAN BANK UMUM SWASTA NASIONAL DI BURSA EFEK INDONESIA - Daniel Sinung K.P., Suprihatmi Sri Wardiningsih & Edi Wibowo (Universitas Slamet Riyadi, 2016)
The purpose of this research was: 1) to analyze the significance of the influence on the profitability of banks against NIM Government and national private commercial banks in Indonesia stock exchange period 2012-2014. 2) to analyze the significance of the influence on the profitability of banks against BOPO Government and national private commercial banks in Indonesia stock exchange period 2012-2014. 3) to analyze the significance of the influence of LDR against profitability at Government banks and national private commercial banks in Indonesia stock exchange period 2012-2014. 4) to analyze the significance of the influence of the NPL against profitability at Government banks and national private commercial banks in Indonesia stock exchange period 2012-2014. 5) to analyze the significance of the influence of NIM, BOPO, LDR and NPL simultaneously against profitability at Government banks and national private commercial banks in Indonesia stock exchange period 2012-2014. Research methods method using case studies, the data type of the data being used is qualitative and quantitative data, the source data used the data of seconds. The population in this research is Government banks and national private commercial banks in Indonesia stock exchange as much as 21 banks, using purposive sampling technique of sampling, namely an amount of 18 banks, methods of data collection used documentation. Technique of data analysis used a classic assumption test, multiple linear regression analysis, t-test, F-test and coefficient of determination. The research results obtained conclusions: 1) partially known that Net Interest Margin (NIM) significant positive effect towards profitability. 2) partially known that operating expenses/operating income (BOPO) significant negative effect towards profitability. 3) partially known that the Loan To Deposit Ratio (LDR) of significant negative effect towards profitability. 4) partially known that Non Performing Loan (NPL) effect is not significantly to profitability. 5) simultaneously can note that Net Interest Margin (NIM), operating expenses/operating income (BOPO), Loan To Deposit Ratio (LDR), and Non-Performing Loan (NPL) have a significant effect on profitability.Keywords: NIM, BOPO, LDR, NPL, profitability.